Accessing the Inaccessible: Redefining Play as a Spectrum - Zosh, Jennifer M.; Hirsh-Pasek, Kathy; Hopkins, Emily J.; Jensen, Hanne; Liu, Claire; Neale, Dave; Solis, S. Lynneth; Whitebread, David (Frontiers in Psychology, 2018)
Defining play has plagued researchers and philosophers for years. From describing play as an inaccessible concept due to its complexity, to providing checklists of features, the field has struggled with how to conceptualize and operationalize “play.” This theoretical piece reviews the literature about both play and learning and suggests that by viewing play as a spectrum – that ranges from free play (no guidance or support) to guided play and games (including purposeful adult support while maintaining playful elements), we better capture the true essence of play and explain its relationship to learning. Insights from the Science of Learning allow us to better understand why play supports learning across social and academic domains. By changing the lens through which we conceptualize play, we account for previous findings in a cohesive way while also proposing new avenues of exploration for the field to study the role of learning through play across age and context.